Effects of hydrothermal treatment of sewage sludge on pyrolysis and steam gasification. (October 2015) - Moon, Jihong; Mun, Tae-Young; Yang, Won; Lee, Uendo; Hwang, Jungho; Jang, Ensuk; Choi, Changsik
Highlights: Hydrothermal treatment (HT) is energy efficient and increases fuel energy density. Pyrolysis and steam gasification were performed with sewage sludge before/after HT. Product gases resembled those from wood chips, particularly at high temperature. HT increases sludge lignin content, possibly enhancing methane yield of product gas. HT can improve sewage sludge for use as an alternative to biomass and fossil fuels. Abstract: Hydrothermal treatment is a promising option for pretreatment drying of organic waste, due to its low energy consumption and contribution to increasing fuel energy density. In this study, the characteristics of hydrothermally treated sewage sludge were investigated, and pyrolysis and steam gasification were performed with the sludge before and after hydrothermal treatment. The overall composition of product gases from treated sludge was similar to that obtained from steam gasification of wood chips, particularly under high-temperature conditions. In addition, the increase in lignin content of sewage sludge following hydrothermal treatment could help enhance methane yield in product gas during pyrolysis and steam gasification. The findings suggest that hydrothermal treatment is an appropriate method for improving sewage sludge for use as an alternative to biomass and fossil fuels.